Association between regulator of telomere elongation helicase1 (RTEL1) gene and HAPE risk: A case-control study. Issue 39 (September 2017) - Rong, Hao; He, Xue; Zhu, Linhao; Zhu, Xikai; Kang, Longli; Wang, Li; He, Yongjun; Yuan, Dongya; Jin, Tianbo
Abstract : Abstract: High altitude pulmonary edema (HAPE) is a paradigm of pulmonary edema. Mutations in regulator of telomere elongation helicase1 ( RTEL1) represent an important contributor to risk for pulmonary fibrosis. However, little information is found about the association between RTEL1 and HAPE risk. The present study was undertaken to tentatively explore the potential relation between single-nucleotide polymorphisms (SNPs) in RTEL1 and HAPE risk in Chinese Han population. A total of 265 HAPE patients and 303 healthy controls were included in our case-control study. Four SNPs in RTEL1 were selected and genotyped using the Sequenom MassARRAY method. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated by unconditional logistic regression with adjustment for gender and age. All P values were Bonferroni corrected, and statistical significance was set at P  < .0025 (.05/20). In allelic model analysis, we found that the allele "G" of rs6089953 and rs6010621 and the allele "A" of rs2297441 were associated with decreased risk of HAPE. In the genetic model analysis, we found that rs6010621, rs6089953, and rs2297441 were relevant to decreased HAPE risk under dominant model (rs6010621: OR = 0.55; 95% CI = 0.39–0.78; P  = .001; rs6089953: OR = 0.68; 95% CI = 0.48–0.96; P  = .027; rs2297441: OR = 0.63; 95% CI = 0.45–0.89; P  = .008, respectively) and additive model (rs6010621: OR = 0.51; 95% CI = 0.46–0.81; P  < .001; rs6089953: OR = 0.72; 95% CI = 0.55–0.95; P  = .022; rs2297441: OR = 0.73; 95% CI = 0.57–0.95; P  = .019, respectively). SNPs rs6010621 remained significant after Bonferroni correction ( P  < .0025). In addition, haplotype "GG, GT, AT" of rs6089953-rs6010621 were detected significantly associated with HAPE risk ( P  < .05), haplotype "GG" remained significant after Bonferroni correction ( P  < .0025). Our findings provide new evidence for the association between SNPs in RTEL1 and a decreased risk HAPE in the Chinese population. The results need further confirmation.